Effect of Intellectual Capital and Corporate Social Responsibility on Firm Value with Tax Avoidance as Moderating Variable - Rantung, Diestri Margaret; Ruslim, Herman (Dinasti Publisher, 2026)
This study examines the impact of intellectual capital and corporate social responsibility (CSR) on firm value, with tax avoidance as a moderating variable. It focuses on primary consumer goods companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. The sample, selected through purposive sampling, includes 37 companies that met specific criteria. Moderated regression analysis (MRA) was performed using Eviews 13 and SPSS 25, with data prepared in Microsoft Excel. The study found that intellectual capital significantly increases firm value, demonstrating that companies using knowledge-based resources effectively see improved market performance and competitive advantage. Conversely, corporate social responsibility (CSR) and tax avoidance showed no significant effects on firm value, indicating these factors did not drive value creation within primary consumer goods firms. Additionally, tax avoidance did not significantly modify the relationship between intellectual capital and firm value, or between CSR and firm value, showing that tax strategies did not impact these relationships.